El Jurista en el Nuevo Mundo : Pensamiento. Doctrina. Mentalidad - Tau Anzoátegui, Víctor (Book collections on Project MUSE., 2016)
The present work addresses the history of Derecho Indiano (Spanish Colonial Law) and proposes to examine the role played by Indiano-Castilian jurists in the New World as creators and enforcers of a science and the practice of law. They were given the task of organising and developing public authorities as well as the new society, and in their engagement with the temporary institutions, they were confronted with realities and situations as diverse as they themselves proclaimed them to be.